Examining Gender Effects on Leadership among Future Managers: Comparing Hofstede’s Masculine vs. Feminine Countries - Gannouni, Kais; Ramboarison-Lalao, Lovanirina (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
This article examines biological gender and gender-role identity effects on self-perceived leadership among 371 future managers, and compares cultural differences linked to Hofstede’s masculine versus feminine countries of origin. The results showed no significant differences in leadership between males and females. For males, masculinity and femininity both correlate with leadership. This is not the case for females. In masculine-cultured countries, masculinity is significantly higher for males, and the results showed a significant correlation between masculinity and leadership. Conversely, in feminine-cultured countries, femininity is higher for females, with a significant correlation between femininity and leadership. Implications of our results are discussed.